Dual role of quercetin in enhancing the efficacy of cisplatin in chemotherapy and protection against its side effects: a review. (2nd November 2022) - Najafi, Masoud; Tavakol, Shima; Zarrabi, Ali; Ashrafizadeh, Milad
Abstract: Chemotherapy has opened a new window in cancer therapy. However, the resistance of cancer cells has dramatically reduced the efficacy of chemotherapy. Cisplatin is a chemotherapeutic agent and its potential in cancer therapy has been restricted by resistance of cancer cells. As a consequence, the scientists have attempted to find new strategies in elevating chemotherapy efficacy. Due to great anti-tumour activity, naturally occurring compounds are of interest in polychemotherapy. Quercetin is a flavonoid with high anti-tumour activity against different cancers that can be used with cisplatin to enhance its efficacy and also are seen to sensitise cancer cells into chemotherapy. Furthermore, cisplatin has side effects such as nephrotoxicity and ototoxicity. Administration of quercetin is advantageous in reducing the adverse effects of cisplatin without compromising its anti-tumour activity. In this review, we investigate the dual role of quercetin in enhancing anti-tumour activity of cisplatin and simultaneous reduction in its adverse effects.